Implementation of Active Learning Strategies In Improving Arabic Language Skills for Students of STAI As-Sunnah Tanjung, North Sumatra - Kamalia Kamalia; Wahyudin Nur Nasution; Sakholid Nasution (STAI Hubbulwathan Duri, 2022)
This study aims to describe the implementation of active learning strategies to speak Arabic as well as various supporting and inhibiting factors, and also to describe the results obtained after implementing active learning strategies to speak Arabic at STAI As-Sunnah Tanjung Morawa Deli Serdang. The research data obtained from primary data and secondary data. The primary data comes from key informants taken from purposive techniques, the data collection instruments used are interview guides, observation guides and match lists. While secondary data comes from journals, books, or magazines that are still related to the object of research. For check data validation using data triangulation. The results obtained from the study are STAI As-Sunnah using an active learning strategy based on the integration of 4 Arabic skills, namely speaking, listening, writing and reading skills. It was also found that there were supporting and inhibiting factors for active learning strategies. Supporting factors such as various lecturer methods that motivate students to be active in learning, the existence of a code of ethics regarding the use of Arabic as the main language, as well as the availability of facilities such as language laboratories. Meanwhile, the inhibiting factor is that there are still lecturers who do not understand active learning strategies, and the lack of commitment and seriousness of lecturers in implementing active learning strategies. The result of the active learning process itself is that 95% of the Language Preparation Program participants can graduate, there are also those who continue their studies in Arabic-speaking countries, there are students who are able to win the Arabic speech competition.